Higher Education and Desistance From Crime - Nicola Hughes (Irish Journal of Academic Practice)
Prisoners are one of the most socially and economically disadvantaged groups in society, with low levels of educational attainment and involvement in higher education. This paper reviews the literature on prisoners and higher education to consider the link between higher education and desistance from crime, utilising Giordano et al's, (2002) theory of cognitive transformation and Mazirow's theory of transformative learning. Higher Education has many advantages for prisoners and former prisoners, providing opportunities to develop new skills, self-respect, resilience and it can also assist in the development of a new identity as a non-offender, and the sense of a new life and how it can be realised. This new identity is an essential feature in desistance from crime and developing a life that is crime free, with new opportunities based on educational achievements, rather than criminal opportunities. Education and learning is, thus, transformational, for the individual prisoner or former prisoner as they desist from crime. There are also many benefits for society in general through a reduction in crime rates, and new sources of social and human capital. This paper will consider the links between higher education as transformative for the individual and desistance from crime.